MINUMAN KERAS PENGARUH MIRAS OPLOSAN TERHADAP GENERASI MUDA DAN LINGKUNGAN MASYARAKAT DI CIKOLE, LEMBANG: PENGARUH MIRAS OPLOSAN TERHADAP GENERASI MUDA DAN LINGKUNGAN MASYARAKAT DI CIKOLE, LEMBANG - Ageng Saepudin Kanda S; Ahmad Riana (CV. KAMPUS AKADEMIK PUBLISING, 2024)
Liquor (miras) is a drink that contains ethanol. Ethanol is a psychoactive substance where if someone consumes it, they will experience the effect of decreasing consciousness. At the moment there is a lot of talk about alcoholic beverages, namely adulterated alcohol. Recently, many victims in Indonesia have died due to adulterated alcohol which, apart from being consumed excessively, is also mixed with other substances. deadly chemicals that should not be intended for human consumption. Of course, this phenomenon is very detrimental because mixed alcohol has a higher risk than regular alcohol and can even cause death for the drinker. In Lembang District, specifically in Cikole Village, adulterated liquor itself has claimed lives, so this problem is very serious and there must be handling so that it doesn't get worse.